Ethical concerns about the applications of artificial intelligence in healthcare practices: an explanatory review - Hassan, Ismail Bile; Hashi, Abdurezak Abdulahi (IIUM PRESS, 2021)
Modern advances in machine learning and artificial intelligence (AI) have greatly improved certain healthcare services both in prevention and treatment of given ailments. Artificial intelligence technologies that benefited healthcare include machine learning, natural language processing, rule-based expert system, physical robots, and robotics process automation. AI has aided medical researchers in modeling research, clinical laboratories, anatomic pathology and reading huge data and designing drugs with reliable accuracy. It helped medical doctors’ interpretation of medical images that are designed to diagnose given illnesses, such as imaging practices of X-ray, MRI and ultrasound diagnoses. Though the use of artificial intelligence and machine-learning algorithms is rapidly growing in various healthcare practices with promising potentials, however the use of computer-generated applications in healthcare sector have raised certain ethical concerns about the safety and reliability of these applications. Similar concerns are made about matters of privacy, security, accountability, fairness, and rights. This paper uses an analytical method and reviews these concerns.